Synthesis of metal nanoparticles and their role in degradation of pesticides/herbicides: a review - Noor Zulfiqar; Muhammad Ali; Fawad Inam; Sarwar Khawaja; Hafiz Ali Raza; Faheem Khan (Discover Applied Sciences)
Abstract The persistent use of pesticides and herbicides in agriculture has led to significant environmental pollution, particularly in soil and water systems. Metal nanoparticles (MNPs) offer a novel and effective approach for the degradation of these pollutants due to their unique properties, including high surface area and enhanced catalytic activity. This review focuses on the synthesis of metal nanoparticles through various methods such as chemical reduction, sol–gel, hydrothermal, and green synthesis, and their application in degrading toxic pesticides and herbicides. Among the most studied nanoparticles are those of iron, silver, copper, and zinc oxides, which have shown remarkable efficiency in removing contaminants through mechanisms like photocatalysis, Fenton reactions, and adsorption. The review also highlights recent advancements in green synthesis as a sustainable method for nanoparticle production, minimizing environmental risks. Despite the promising results, issues related to nanoparticle toxicity, stability, and scalability in large-scale applications remain a challenge. Addressing these concerns through innovative synthesis techniques and further research is crucial for the future of nanoparticle use in environmental remediation. Metal nanoparticles present an eco-friendly alternative for agricultural pollution control, offering significant potential for mitigating the harmful effects of pesticides and herbicides. Graphical Abstract